All Is not English that Glitters: False Anglicisms in the Spanish Language of Sports. - CAMPOS-PARDILLOS, MIGUEL ÁNGEL (Atlantis (0210-6124))
Over the past decades, many studies have dealt with Anglicisms in Spanish, not only in science and technology, but also in other areas such as business, fashion and even sports. However, in spite of the large number of works on Spanish Anglicisms in sports, these have often disregarded the distinction between Anglicisms and false Anglicisms. Given their importance as evidence of the particular relationships between languages, this article focuses on the use of false Anglicisms in the Spanish language of sports, which has not only adopted English words giving them new meanings and usage, but has also either imported items with an English appearance from other languages or created its own forms based on English patterns. Although these false Anglicisms, which have proven extremely popular in various European languages (not only Spanish), have frequently been used and disseminated, as some examples will prove, little attention has been paid to their differences with the English term or their non-English origin.